Hadith Inspirational Design Thinking of Moral Cultivation of Adolescents - Tiara Azzahra Hidayah; Ahmad Gibson Al Bustomi (Gunung Djati Conference Series, 2021)
This study aims to discuss the basis for good moral development in adolescents. This research method uses a qualitative type through literature and field studies with a design thinking approach. The results of this discussion include the role of parents or teachers in instilling good morals in adolescents who currently need good intake. The results of this study concluded that the hadith of the Prophet SAW has inspirational messages in fostering good morals in adolescents